Pesticide Uses and its Effects on Public Health and Environment - Gyawali, Kalpana (Journal of Health Promotion, 2018)
Pesticide’s manufacture, use, storage and disposal should be strictly regulated to reduce its negative effects on environment and public health. The reports show that the pesticide use increasing every year globally and currently its national use in average is 0.39 kg a. i/ha. It has been found that the quantity of consumption of pesticide in Nepal in agricultural field is very low in comparison to the other countries of the globe but due to its haphazard use in some commodity and ignorance of waiting period after its application has increased the risk of the exposure of farm families to pesticides and intake of pesticides by consumers, which are becoming major health threat. Journal of Health Promotion Vol.6 2008, p.28-36